A multifactorial analysis of phonetic word stress correlates in Standard Lithuanian: verification of the prosodic element interaction model - Švageris, Evaldas (Baltistica, 2025)
This article aims to verify the empirical background of the phonetic interaction of prosodic elements in Standard Lithuanian – specifically word stress and phrase intonation. A multifactorial (MANOVA) analysis of F0 dynamics was performed to achieve this, revealing that the ratio of three acoustic parameters (F0 range, F0 jerk, and duration) depends on word stress. The speaker‘s intention to distinguish a syllable from its environment prosodically can be associated with a relatively wider F0 range, its more linear modulation, and a longer duration of the sound. The overall picture of F0 dynamics correlates with the position of the stress within the word. The primary phonetic cue for achieving the effect of a stressed final syllable is the static phonation of adjacent pre-stressed syllables (F0 acceleration →0 resulting in F0 jerk →0 and reduced syllable duration →0). The need to highlight intersyllabic differences in dynamic F0 profiles diminishes when the word stress is on the first syllable, leading to the assumption that the absolute beginning of the word, under phonetic ceteris paribus, acquires greater relative weight from a prosodic point of view. Bearing this in mind, one can conclude that the same F0 dynamics reflect the interaction of prosodic elements. The only distinction is that the intonational factor determines the overall change of F0, while the word stress controls its (intra)syllabic dynamics (variation of F0 over time).